FENOMENA BAHASA PADA RUANG PUBLIK SEPANJANG JALAN PROTOKOL KOTA PONTIANAK - Wahyu Damayanti (Balai Bahasa Sumatera Utara, 2019)
The priority of the country's language becomes a reflection that the city upholds Indonesian language. This does not rule out the possibility of the Pontianak city government. This paper tries to explain the phenomenon of language in public spaces along the Pontianak city protocol. The aim is to describe the use of language and find out the level of language control in Pontianak city public spaces. This research method uses a combination of quantitative methods and qualitative methods. Quantitative method is used as a method of processing the number of population and corpus of data to determine the number of data samples. The qualitative method is used as a method of analyzing the linguistic features of data samples which include the type of language landscape and language use of data samples. The data source of this research is the primary data source directly collected directly from the area along the Pontianak city protocol streets. Data were classified and analyzed according to the study. Data analysis in this study was presented using descriptive analytic methods. The results of the study are the existence of language shifts that can be seen from the emergence of complete foreign language interference, grammatical interference, the use of foreign terms in the structure of language and code-switching in foreign language. The level of language control along the protocol road in the public sphere has a significant result, B, which means that the state language is still controlled at the level of public space.